2007
DOI: 10.1016/j.compstruct.2006.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aluminum closed-cell foam filling on the quasi-static axial crush performance of glass fiber reinforced polyester composite and aluminum/composite hybrid tubes

Abstract: The effect of Al closed-cell foam filling on the quasi-static crushing behavior of an E-glass woven fabric polyester composite tube and thin-walled Al/polyester composite hybrid tube was experimentally investigated. For comparison, empty Al, empty composite and empty hybrid tubes were also tested. Empty composite and empty hybrid tubes crushed predominantly in progressive crushing mode, without applying any triggering mechanism. Foam filling was found to be ineffective in increasing the crushing loads of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…In contrast to the metal tubes, Very few studies [15][16][17][18] have been conducted on composite tubes with foam-filler material. Guden et al [16] studied the effect of aluminium closed-cell foam filling on the quasi-static crushing behaviour of E-glass woven fabric polyester composite tubes and thin-walled aluminium/glass polyester composite hybrid tubes. They concluded that the foam filling of hybrid tubes resulted into an axial splitting of the outer composite tubes due to the resistance imposed by the aluminium tube.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the metal tubes, Very few studies [15][16][17][18] have been conducted on composite tubes with foam-filler material. Guden et al [16] studied the effect of aluminium closed-cell foam filling on the quasi-static crushing behaviour of E-glass woven fabric polyester composite tubes and thin-walled aluminium/glass polyester composite hybrid tubes. They concluded that the foam filling of hybrid tubes resulted into an axial splitting of the outer composite tubes due to the resistance imposed by the aluminium tube.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this ductile failure mode was usually found in the steel tubes filled with [19,20]. In addition, it was also observed in the effect of Al closed foam filling on the quasi-static crushing behavior of an E-glass woven fabric polyester composite tube, and the results indicated that Al foam filling stabilized the composite progressive crushing model [21].…”
Section: Failure Modes and The Bearing Capacitymentioning
confidence: 84%
“…It was reported that CFRP provides restraints to the development of elastic buckling deflection which results into delay in local buckling of the material. Guden et al [56] conducted an experimental investigation to check the effect of Al closed-cell foam filling on the quasi-static crushing behavior of an E-glass woven fabric composite and Al metal/composite hybrid tubes. They observed two types of crushing mode, namely progressive and catastrophic.…”
Section: Metal -Composite (Hybrid) Type Energy Absorbermentioning
confidence: 99%